Study Protocol—Coping With the Pandemics: What Works Best to Reduce Anxiety and Depressive Symptoms - Fortea, Lydia; Solanes, Aleix; Pomarol-Clotet, Edith; Garcia-Leon, Maria Angeles; Fortea, Adriana; Torrent, Carla; Varo, Cristina; Bonnin, C. Mar; Montejo, Laura; Alonso, Jordi; Carmona, Susana; Soldevila-Matías, Pau; et al. (Frontiers in Psychiatry, 2021)
Background: The coronavirus disease 2019 (COVID-19) pandemic and lockdown might increase anxiety and depressive symptoms in most individuals. Health bodies recommend several coping behaviors to protect against such symptoms, but evidence on the relationship between these behaviors and symptoms mostly comes from cross-sectional studies in convenience samples. We will conduct a prospective longitudinal study of the associations between coping behaviors and subsequent anxiety and depressive symptoms during the COVID-19 pandemic in a representative sample of the Spanish general adult population. Methods: We will recruit 1,000 adult participants from all autonomous communities of Spain and with sex, age, and urbanicity distributions similar to those of their populations and assess anxiety and depressive symptoms and coping behaviors using fortnightly questionnaires and real-time methods (ecological momentary assessments) for one year. The fortnightly questionnaires will inquire about anxiety and depressive symptoms (General Anxiety Disorder-7 (GAD-7) and Patient Health Questionnaire-9 (PHQ-9)) and the frequency of ten potential coping behaviors (e.g., follow a routine) during the past two weeks. In addition, we will collect several variables that could confound or moderate these associations. These will include subjective well-being (International Positive and Negative Affect Schedule Short Form (I-PANAS-SF) and Satisfaction with Life Scale (SWLS)), obsessive-compulsive symptoms (Obsessive Compulsive Inventory-Revised (OCI-R)), personality and emotional intelligence (International Personality Item Pool (IPIP) and Trait Emotional Intelligence Questionnaire Short Form (TEIQue-SF)), sociodemographic factors (e.g., work status, housing-built environment), and COVID-19 pandemic-related variables (e.g., hospitalizations or limitations in social gatherings). Finally, to analyze the primary relationship between coping behaviors and subsequent anxiety and depressive symptoms, we will use autoregressive moving average (ARMA) models. Discussion: Based on the study results, we will develop evidence-based, clear, and specific recommendations on coping behaviors during the COVID-19 pandemic and lockdown. Such suggestions might eventually help health bodies or individuals to manage current or future pandemics.